Organizational Commitment, Culture, and Green Training and Their Effects on Performance via Work Engagement: A Systematic Literature Review - Wenny Desty Febrian; Indra Sani (Goodwood Publishing, 2026)
Purpose: This study examines the effects of organizational commitment, organizational culture, and green training on employee performance, with work engagement as a mediating mechanism in the Micro, Small, and Medium Enterprises (MSME) sector. Research Methodology: A Systematic Literature Review (SLR) was conducted to synthesize evidence from peer-reviewed international publications indexed in Scopus, Web of Science, Emerald, Springer, and Google Scholar. Relevant studies were screened and analyzed using a structured process involving data reduction, matrix-based data display, and comparative synthesis to identify patterns, consistencies, and divergences across the studies. Results: The review indicates that organizational commitment, culture, and green training positively impact employee performance, both directly and indirectly, through work engagement. Affective, normative, and continuance commitment enhance emotional and cognitive involvement, whereas supportive organizational cultures and green training boost employee competencies, leading to improved performance outcomes. Conclusions: Work engagement is a crucial mediating factor linking organizational commitment, culture, and green training to enhanced employee performance. Fostering engagement is essential for improving MSME performance. Limitations: As a literature-based study, the findings are subject to limitations in generalizability and require validation through empirical research using primary data. Contributions: This study developed an integrative conceptual framework that combines organizational commitment, organizational culture, and green training, highlighting work engagement as a psychological pathway to sustainable employee performance. This study extends the human resource management literature, particularly in MSME contexts, where resource constraints necessitate effective internal capability development.